SECTOR – Greenhouse Gases (GHG) calculation tool for specific use in rice systems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The calculation tool has been developed internally and tested with different data sets from case studies in different countries and for proposal preparation. The tool has been published and can be accessed and downloaded by anybody.